PATIENT-CENTERED CARE IN CLINICAL NURSING SETTINGS: A LITERATURE REVIEW - Heri Siswanto; Nurfika Asmaningrum; Rondhianto Rondhianto (UNEJ e-Proceeding, 2023)
Background: Optimal health services are one indicator of success in measuring the quality of health services. Patient-focused health services are a service model implemented in hospitals. This study aims to determine the concept of patient-centered care and its implementation in hospitals. Methods: The method of this study is a literature review. This study used electronic databases such as PubMed, Google Scholar,and Science Direct. Literature review was conducted on international journals published in the last 5 years, available in full text and not the result of a review. The keywords used are “Patient Centered care and hospital. Results: The results showed that patient-focused health services to contribute for improving patient-focused services by helping organizations target quality management efforts and can improve patient adherence in treatment so as to reduce healthcare costs. PCC also contributes to improving the performance of health service professionals and increasing patient and family participation in decision-making regarding the health services to be provided. The PCC method is very effective in palliative care and less effective in emergency care and intensive care units. Conclusion: Patient-centered care includes aspects of caring that respect values, patient needs, patient-based decision making, and patient preferences process of planning, and implementing care. Patient-centered care has advantages which include: reducing the length of stay thereby minimizing the cost of care incurred by the patient and increasing the trusting relationship between the health care team and the patient. The patient-centered care model is also an indicator to measure the level of patient satisfaction with health services.